PENERAPAN NILAI-NILAI PHBS DALAM RUMAH TANGGA DI KELURAHAN SUNGAI BANGKONG KOTA PONTIANAK - Anggriani, Gina Dwi; Imran, Imran; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of this research "Application of Clean and Healthy Living Behavior in the Household in Sungai Bangkong Village, Pontianak City". This study aims to find out the general problems in this study, namely "How to apply the values of clean and healthy living behavior in households Sungai Bangkong Village". With the sub-problems: 1) What are the values of clean and healthy behavior in the household in the Sungai Bangkong. 2) What is the application of clean and healthy behavioral values in the household. The form of research used in this study is qualitative research with descriptive research methods. Data collection techniques used observation, interview and documentation techniques. The results of this study are that the application of the values of clean and healthy living behavior in households in theontongak city sungai bangkong village can be concluded to be implemented quite well, although there are several indicators or PHBS values that are still not maximal in its application. Such as lack of fruit consumption everyday, combating mosquito larvae only a few times, as well as the presence of family members who smoke inside the house, and their lack of knowledge about what PHBS actually is because there is no socialization from the health authorities about promoting PHBS in the household.Â Keywords:Â  Application, Value, PHBS, Household, Sungai Bangkong